Evaluation of Technical Aspects of Health and Welfare of Intensively Raised Goats in Kendari City - Wijaya, Trisna; Asminaya, Nur Santy; Libriani, Restu (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
This study aims to evaluate the technical aspects of the health and welfare of goats that are intensively raised in Kendari City. The research method used is the survey method. The determination of the research location was carried out by purposive sampling, then in each sub-district the determination of respondents was carried out using the snowball sampling method. The data was analyzed descriptively. The results of the study showed that disease prevention measures and the provision of deworming drugs in Abeli, Nambo and Poasia Sub-districts were in the bad category while disease treatment in Abeli Sub-district was in the good category and in Nambo and Poasia Sub-districts was in the fairly good category. In terms of animal welfare, in general it was in the fairly good category in Abeli, Nambo and Poasia Sub-districts. Breeders need to be given training and socialization to breeders about the importance of aspects of animal health and welfare in increasing livestock productivity. The conclusion of the study is that the technical aspects of the health and welfare of goats that are intensively raised are in the fairly good category so they need improvement